Development of Assessment Instruments Based on Liveworksheet On the Material of Respiratory System of Class XI MIA 3 MA Students Madani Alauddin Pao-Pao: Pengembangan Instrumen Penilaian Berbasis Liveworksheet Pada Materi Sistem Pernapasan Siswa Kelas XI MIA 3 MA Madani Alauddin Pao-Pao - Jufri, Fahri Amalia; Syamsudduha, St.; Ali, Ahmad (Al-AHYA: Jurnal Pendidikan Biologi, 2025)
This study was conducted with the aim of designing and developing a liveworksheet-based evaluation instrument and assessing its quality in the Respiratory System material for grade XI MIA 3 MA Madani Alauddin Pao-pao students. The quality of the instrument was analysed based on the aspects of validity, reliability, discriminating power, level of difficulty, and effectiveness of distractors in each item. This study adapted the development model proposed by Tessmer, which falls under the category of Formative Research. The development procedure consisted of three main stages, namely the initial stage, the self-evaluation stage which included analysis and design activities, and the prototyping stage which consisted of expert review, individual testing, small group testing, and field testing. The subjects of this study were grade XI MIA 3 MA Madani Alauddin Pao-pao students. The results showed that the content validity coefficient reached 1, indicating a very high level of validity. Of the total 25 items, 44% were declared empirically valid, while 56% were classified as invalid. The reliability test using the KR-20 formula produced a value of 0.99, indicating very high reliability. The discrimination power analysis showed that 36% of the items were in the very poor category, 36% were poor, 24% were adequate, and only 4% were good. Based on the level of difficulty, 84% of the items were categorised as easy and 16% as moderate. The results of the distractor effectiveness analysis showed that most distractors were not functioning optimally, with 24% very poor, 28% poor, 8% not very good, 20% good, and 20% very good.